Combined Analysis of RRBS DNA Methylome and Transcriptome Reveal Novel Candidate Genes Related to Porcine Clostridium perfringens Type C-Induced Diarrhea - Huang, Xiaoyu; Yang, Qiaoli; Yan, Zunqiang; Wang, Pengfei; Shi, Hairen; Li, Jie; Shang, Xuefeng; Gun, Shuangbao (Frontiers in Genetics, 2022)
Clostridium perfringens type C (Cp) is one of the principal microorganisms responsible for bacterial diarrhea in neonatal and pre-weaning piglets. To better understand the molecular effects of Cp infection, we performed a genome-wide comparison of the changes in DNA methylation and gene expression in Cp infected resistant and susceptible piglets. We characterized the pattern of changes in methylation and found 6485, 5968 and 6472 differentially methylated regions (DMRs) of piglets infected with Cp in IR vs IC, IS vs IC and IS vs IR groups, respectively. These methylation changes for genes mainly involved in immune and inflammatory responses, cell adhesion and activation of transcription factors. Gene ontology and KEGG pathway analyses showed that the differentially methylated genes (DMGs) were associated with negative regulation of transcription, apoptotic processes, protein binding, kinase activity. And were enriched in immunity related pathways, such as MAPK signaling pathway, Toll-like receptor signaling pathway, NF-kappa B signaling pathway. Integrative analysis identified 168, 198 and 7 mRNAs showing inverse correlations between methylation and expression with Cp infection. Altered DNA methylation and expression of various genes suggested their roles and potential functional interactions upon Cp infection, 14 immune associated mRNAs with differential methylation and transcriptional repression were identified in IS vs IR, commonly revealing that the differential expressed genes (DEGs) LBP, TBX21, and LCN2 were likely involved in the piglets against to Cp infection. The present results provide further insight into the DNA methylation epigenetic alterations of C. perfringens type C infected piglet ileum tissues, and may advance the identification of biomarkers and drug targets for predicting susceptibility to and controlling C. perfringens type C induced piglet diarrhea.